Factors associated with oral anticoagulant non-use at first ischemic stroke in atrial fibrillation: A nationwide study - Vilpponen, Marko; Aro, Aapo L.; Halminen, Olli; Tiili, Paula; Linna, Miika; Luojus, Alex; Teppo, Konsta; Mustonen, Pirjo; Haukka, Jari; Hartikainen, Juha; Airaksinen, K. E. Juhani; Lehto, Mika; et al. (SAGE PUBLICATIONS LTD, 2025)
Background:
Limited data exist on characteristics and patterns associated with patients with atrial fibrillation (AF) who encounter first-ever ischemic stroke (IS) while not on oral anticoagulation (OAC) therapy.
Methods:
From a nationwide registry-linkage database including all patients with AF in Finland from 2007 to 2017, we included those with IS after diagnosis of AF and those without IS. Factors associated with non-OAC use among IS patients were examined using logistic regression, with separate models for independent variables and risk scores.
Results:
Among 174,094 patients with new-onset AF, 11,680 (6.7%) patients (56.9% female; mean age 79.0 years) experienced IS. A total of 7507 (64.3%) of IS patients were not on OAC at the time of IS (mean age 78.9 years; 57.2% female). The proportion of non-OAC decreased from 77.2% to 45.6% over the study period. In the adjusted logistic regression model, the strongest factor associated with non-OAC was CHA2DS2-VA score of 0 points (OR 4.561; 95% CI, 3.097–6.718), followed by a score of 1 point (OR 2.382; 95% CI, 1.971–2.879). Other significant independent factors associated with non-OAC use were alcohol abuse (OR 2.282; 95% CI, 1.805–2.885), liver dysfunction (OR 2.120; 95% CI, 1.335–3.367), renal dysfunction (OR 1.430; 95% CI, 1.200–1.703), dementia (OR 1.394; 95% CI, 1.227–1.583), prior myocardial infarction (OR 1.346; 95% CI, 1.181–1.535), age <65 years (OR 1.274; 95% CI, 1.034–1.571), lowest income (OR 1.232; 95% CI, 1.104–1.374), female sex (OR 1.177; 95% CI, 1.077–1.287), and antiplatelets/NSAID use (OR 1.133; 95% CI, 1.042–1.231).
Conclusions:
Less than 2% of AF patients experienced IS during study period and among these around 63% were without appropriate OAC therapy at the time of the IS. However, decreasing trend of non-OAC use was identified throughout the study period.